Neko: A Modern, Portable, and Scalable Framework for Extreme-Scale Computational Fluid Dynamics - Jansson, Niclas; Karp, Martin; Markidis, Stefano; Schlatter, Philipp (Proceedings - 2024 IEEE International Conference on Cluster Computing Workshops, CLUSTER Workshops 2024, 2024)
Recent trends and advancements in including more diverse and heterogeneous hardware in High-Performance Computing are challenging scientific software developers in their pursuit of good performance and efficient numerical methods. As a result, the well-known maxim 'software outlives hardware' may no longer necessarily hold true, and researchers are today forced to re-factor their codes to leverage these powerful new heterogeneous systems. We present Neko - a portable framework for high-fidelity spectral element flow simulations. Unlike prior works, Neko adopts a modern object-oriented Fortran 2008 approach, allowing multi-tier abstractions of the solver stack and facilitating various hardware backends ranging from general-purpose processors, accelerators down to exotic vector processors and Field Programmable Gate Arrays (FPGAs) via Neko's device abstraction layer. Focusing on Neko's performance and exascale readiness, we outline the optimisation and algorithmic work necessary to ensure scalability and performance portability across a wide range of platforms. Finally, we present performance measurements on a wide range of accelerated computing plat-forms, including the EuroHPC pre-exascale system LUMI and Leonardo, where Neko achieves excellent parallel efficiency for an extreme-scale direct numerical simulation (DNS) of turbu-lent thermal convection using up to 80% of the entire LUMI supercomputer.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Accelerators; Direct numerical simulation; Spectral element method